Collectivism Is Associated With Greater Neurocognitive Fluency in Older Adults - Medina, Luis D.; Sadler, Melody; Yeh, May; Filoteo, J. Vincent; Woods, Steven Paul; Gilbert, Paul E. (Frontiers in Human Neuroscience, 2019)
Neuropsychological research has been limited in representation of cultural diversity due to various issues, raising questions regarding applicability of findings to diverse populations. Nonetheless, culture-dependent differences in fundamental psychological processes have been demonstrated. One of the most basic of these, self-construal (individualism, collectivism), is central to how many other differences are interpreted. Self-construals may have possible consequences on social interactions, emotions, motivation, and cognition. This study aimed to evaluate the impact of self-construal on neurocognitive functions in older adults. A total of 86 community-dwelling older adults 60 years and older were assessed with three common self-report measures of self-construal along individualism and collectivism (IC). A cognitive battery was administered to assess verbal and non-verbal fluency abilities. Latent profile analysis was used to categorize individuals according to IC, and one-way analyses of covariance (ANCOVA), including relevant covariates (e.g., ethnicity, gender, linguistic abilities), were used to compare neurocognitive functions between individualists and collectivists. Collectivists outperformed individualists on left frontally-mediated measures of verbal fluency (action, phonemic) after controlling for relevant covariates, F1, 77=6.942, p=0.010, η2=0.061. Groups did not differ on semantic fluency, non-verbal fluency, or attention/working memory (all ps>0.05). These findings suggest a cognitive advantage in collectivists for verbal processing speed with additional contribution of left frontal processes involved in lexicosemantic retrieval. Self-construal may provide a meaningful descriptor for diverse samples in neuropsychological research and may help explain other cross-cultural differences.